Distribution, Diversity, and Soil Associations of Wine Grape Plant-Parasitic Nematodes in Georgia, U.S.A., Vineyards - Martin, Katherine F (Plant disease, 2023)
Wine grape (Vitis vinifera and V. vinifera hybrids) production in Georgia occurs in three distinct regions (North, West, and South) which can be characterized by sandy, sandy-loam, or sandy clay-loam soils. We studied plant-parasitic nematode (PPN) communities in 15 wine grape vineyards from the three primary growing regions to understand which nematodes are a concern and what soil characteristics are associated with their occurrence and relative abundance. Twelve genera of PPNs were detected throughout the state: Belonolaimus, Helicotylenchus, Hemicycliophora, Heterodera, Hoplolaimus, Meloidogyne, Mesocriconema, Paratrichodorus, Paratylenchus, Pratylenchus, Tylenchorhynchus, and Xiphinema. Nonmetric multidimensional scaling ordination and multirank permutation procedure identified PPN community differences and soil characteristics that were associated by region. Indicator species analysis identified Helicotylenchus, Mesocriconema, Tylenchorhynchus, and Xiphinema as statistically associated with the West while Meloidogyne and Paratrichodorus were associated with the South. Our analyses further suggested that soil texture (percent sand, percent clay, and percent silt) and the lime buffer capacity at equilibrium (LBCEQ) were associated with PPN community structure while pH was not. When focused on a single vineyard in the North, multiple logistic regression analysis suggested a statistically significant association between Meloidogyne spp. and soil characteristics, including percentages of sand, pH, and LBCEQ. Our study supports the association between soil characteristics and specific nematode genera, as well as the emergence of LBCEQ, the soil measurement with the strongest statistical association with nematode community structure and Meloidogyne presence